2010
DOI: 10.1016/j.brat.2010.05.004
|View full text |Cite
|
Sign up to set email alerts
|

A randomised worksite comparison of acceptance and commitment therapy and stress inoculation training

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. In this comparative intervention study, 107 working individuals with above average levels of distress were randomly assigned to one of three conditions: acceptance and commitment therapy (ACT; n = 37); stress inoculation training (SIT; n = 37); or a waitlist control group (n = 33). The interventions were delivered to small groups in the workplace via two half-day training sessions. ACT and SIT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
101
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 162 publications
(117 citation statements)
references
References 33 publications
11
101
0
4
Order By: Relevance
“…Findings indicating that ACT led to significant improvements in employees' emotional burnout and strain, and that increases in psychological flexibility mediated the improvements observed in the exhaustion component of burnout, are consistent with both Psychological Mechanisms ACT theory (Hayes, 1987;Hayes et al, 1999), and ACT worksite intervention research (Bond & Bunce, 2000;Flaxman & Bond, 2010). Our findings thus lend support to the growing evidence base demonstrating the beneficial impact of increasing psychological flexibility on workers' mental health.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Findings indicating that ACT led to significant improvements in employees' emotional burnout and strain, and that increases in psychological flexibility mediated the improvements observed in the exhaustion component of burnout, are consistent with both Psychological Mechanisms ACT theory (Hayes, 1987;Hayes et al, 1999), and ACT worksite intervention research (Bond & Bunce, 2000;Flaxman & Bond, 2010). Our findings thus lend support to the growing evidence base demonstrating the beneficial impact of increasing psychological flexibility on workers' mental health.…”
Section: Discussionsupporting
confidence: 83%
“…In addition to our predictions regarding improvements in emotional burnout and strain, it is important to consider the psychological mechanisms by which these changes may occur. As previously explained, research has indicated that psychological flexibility is the mechanism, or mediator, by which ACT interventions improve strain (Bond & Bunce, 2000;Flaxman & Bond, 2010); therefore, in the present study we may expect to find this same mediation effect. Since the emotional exhaustion component of burnout is often considered to be synonymous with strain (Maslach, 2003;Maslach et al, 2001), we may expect to find that increases in psychological flexibility also mediate improvements in this outcome.…”
Section: Identifying the Mechanisms Underlying Emotional Burnout Allesupporting
confidence: 73%
See 2 more Smart Citations
“…A contemporary cognitive and behavioural approach, Acceptance and Commitment Therapy (ACT said as a word rather than three letters), has a growing body of research indicating its effectiveness within the working population (Bond & Bunce, 2000;Flaxman & Bond, 2010b;Hayes et al, 2004).…”
Section: Introductionmentioning
confidence: 99%